Dietary counseling intervention for female heavyweight judo athletes decreased cardiometabolic risk - Murata, H.; Oshima, S.; Torii, S.; Sakamoto, S.; Taguchi, M.; Higuchi, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: There is a concern that some heavyweight (HW) Judo athletes have high cardiometabolic risk (CMR) due to excess body fat mass (FM) along with their large body mass (BM). Our previous study showed that female HW Judo athletes had high FM and some of them developed insulin resistance (IR) (Murata, et al., 2013). Visceral fat (VF) and IR have been shown as main contributors of CMR (Despres, et al., 2008) and our previous study showed that a dietary counseling intervention (DCI) for male HW Judo athletes decreased CMR by decreasing VF (Murata, et al, 2015). Therefore, the purpose of this study was to examine whether DCI for female HW Judo athletes can effectively decrease CMR without reducing their physical performance. Methods: Fourteen female Judo athletes who belonged to 78kg and over 78kg classes participated in this study. They were divided into 2 groups such as DCI group [n=7; age: 20.1±1.3 years, BM: 80.3(78.7-107.3)kg] and control (CONT) group [n=7; 20.1±0.6 years, 82.8(78.0-92.0) kg]. DCI group completed a 10-week DCI using e-mail and personal interview by the certified Sports Dietitian which instructed them to have a well-balanced diet with proper caloric intake. VF and body composition were assessed by magnetic resonance imaging and dual energy X-ray absorptiometry, respectively. Physical fitness was also examined by hand grip strength (HGS) and the 20-m shuttle run (SR) test. Results: After DCI, reductions of %BF (from 29.3±5.8% to 27.8±6.1%) and FM in DCI group were significantly larger than CONT group (p<0.05), whereas increases of total fat-free mass (FFM), HGS and the number of SR in DCI group were significantly larger than CONT group. HOMA-IR in DCI group was also significantly decreased compared to CONT group (p<0.01). Discussion: It was found that the 10-week DCI for female HW Judo athletes significantly lowered %BF, FM and HOMA-IR with increasing FFM, muscle strength as well as cardiorespiratory fitness. Interestingly DCI group did not significantly decrease VF. Previous study showed that overweight men deceased larger VF than overweight women in calorie restriction with exercise (Redman, et al., 2007). Therefore, although DCI effectively reduces CMR for female HW Judo athletes, it may have less effect on reducing VF for female HW Judo athletes. Conclusion DCI for female HW Judo athletes reduced CMR without reducing their physical performance.